2009
DOI: 10.1108/00251740910938894
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of intellectual capital disclosure: evidence from Australia

Abstract: Purpose-The purpose of this paper is to examine determinants of the decision to disclose intellectual capital in annual reports. Design/methodology/approach-The paper derives theoretical predictions from the previous literature and bases the study on archival data with a sample of 125 publicly listed Australian firms. The authors perform a content analysis of annual reports and complement the data with quantitative data from the sample firms. Findings-The paper finds that industry type plays a key role as a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
233
3
24

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(284 citation statements)
references
References 33 publications
24
233
3
24
Order By: Relevance
“…The congress categorized the 36 terms into three categories; (a) human capital; (b) structural capital and (c) relational capital. Because of the presence of some general terms related to the field of intellectual capital, Bruggen (2009) in his study modified the model by placing additional terms into the fourth category called "General Terms". None of relational capital terms appear in the sample firm's annual report.…”
Section: Measurement For Intellectual Capital Disclosure (Dependent Vmentioning
confidence: 99%
See 1 more Smart Citation
“…The congress categorized the 36 terms into three categories; (a) human capital; (b) structural capital and (c) relational capital. Because of the presence of some general terms related to the field of intellectual capital, Bruggen (2009) in his study modified the model by placing additional terms into the fourth category called "General Terms". None of relational capital terms appear in the sample firm's annual report.…”
Section: Measurement For Intellectual Capital Disclosure (Dependent Vmentioning
confidence: 99%
“…To date, various studies has been done by many researchers to examine the determinants of intellectual capital disclosure around the world such as (Taliyang, 2011;Bruggen, 2009;White et al, 2007;Zaludin, 2007;Ousama Anam, 2007, Garcia-Meca et al, 2005 and many more. It can be concluded that a few variables such as company age, size, profitability and growth can be considered as control variables and significantly influence the level of intellectual capital disclosure for the companies.…”
Section: Intellectual Capital Disclosurementioning
confidence: 99%
“…Previous research such as Brennan (2001), Bozzolan et al (2003) and Bruggen et al (2009) found that industry type is an important factor for external IC disclosures as IC is in some industries more important than in others. However, Bontis et al (2000) found that IC has a significant relationship with business performance regardless of industry sector among…”
Section: Industry Typementioning
confidence: 99%
“…Size was found to have a significant impact on the level of external IC disclosures in most studies (Bozzolan et al, 2003;Guthrie et al, 2006;Beaulieu et al, 2002;Bruggen et al, 2009). But, not all studies conclude that the size of the company is a significant factor in explaining voluntary publication of information (Bukh et al, 2003).…”
Section: Firm Sizementioning
confidence: 99%
“…It can be broadly classified into (1) the research on factors which have an impact on intellectual capital disclosures (e.g. size of the organisation and industry type (Brüggen et al, 2009;Whiting & Woodcock, 2011), firm age (White et al, 2007;Sonnier et al, 2009), corporate governance (Li et al, 2008;Hidalgo et al, 2011;Haji & Ghazali, 2013), listing status (Williams, 2001)), and (2) the research which assesses the impact of intellectual capital disclosures on different areas of organisation's performance and its valuation. The latter research provides evidence on, for example, significant and positive effect of intellectual capital disclosures on market capitalization and firm value (Abdolmohammadi, 2005;Orens et al, 2009), the impact of intellectual capital disclosures on the reduction of information asymmetry (Orens et al, 2009;An et al, 2011) and (consequently) the impact of voluntary intellectual capital disclosures on the reduction of the cost of equity capital (Orens et al, 2009;Boujelbene & Affes, 2013;Mangena et al, 2010Mangena et al, , 2016.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%